Dynamic monitoring of platelet activation and its role in post-dissection inflammation in a canine model of acute type A aortic dissection. Issue 1 (December 2016) - Qin, Chaoyi; Zhang, Hongwei; Gu, Jun; Xiao, Zhenghua; Yang, Qin; Meng, Wei
Abstract Background To confirm the activation of platelets (PLT) and explore the role of activated PLT in post-dissection inflammation. Method An acute type A aortic dissection (AAD) canine model was established. Mean platelet volume/platelet count (MPV/PTC), platelet size distribution width (PDW), and inflammatory cytokines (tumor necrosis factor-α [TNF-α] and interleukin-6 [IL-6]) were measured between anesthetization and thoracotomy (T1), at the end of the operation (T2), and at 2 h (T3), 4 h (T4), and 6 h (T5) after the operation. Bivariate analysis was used to determine the correlations between the peak MPV/PTC, PDW, and inflammatory cytokines at T4. Result An AAD canine model was successfully established. Both MPV/PTC and PDW values were significantly higher at T3-T5 than at T1 (P  < 0.05). Both were also significantly higher at T3-T5 in the dissection group than in the sham operation (SO) group (P  < 0.05). Inflammatory cytokine levels were remarkably higher at T3-T5 than at T1, and were higher at T3-T5 in both the dissection and the SO group (P  < 0.05). Bivariate analysis demonstrated positive correlations between MPV/PTC and both TNF-α (r  = 0.826, P  = 0.011) and IL-6 (r  = 0.806, P  = 0.016). Conclusion Activated PLT were identified after AAD, and played a critical role in the initiation of post-dissection inflammation.